К 100-летию Института механики им. С. П. Тимошенко: книги (монографии и учебники) сотрудников Института - Гузь, А.Н.; Рущицкий, Я.Я. (Прикладная механика, 2018)
Статья касается столетнего юбилея Национальной академии наук Украины и Института механики им. С.П.Тимошенко (1918 - 2018) и представляет собой продолжение посвященной этому юбилею статьи из предыдущего номера журнала. Стаття стосується сторічного ювілею Національної академії наук України та Інститута механіки ім. С.П.Тимошенка (1918 – 2018) і являє собою продовження присвяченої цьому ювілею статті з попереднього номера журнала. Запропоновано список найбільш важливих наукових книг, опублікованих за майже сторічний період наукової діяльності працівників Інститута механіки Національної академії наук України ім. С.П.Тимошенка. Стаття включає попередню інформацію, далі список наукових узагальнених колективних багатотомних видань, класичних наукових монографій, підручників, навчальних посібників і деяких інших продуктів видавничої діяльності працівників інститута. У цілому, список нараховує 468 книг. Значна частина цих книг – 247 – представлена в Бібліотеці Конгресу США. This article can be considered as some continuation – renovation, revision and extension – the previous publication of authors on this topic. It is caused by the forthcoming centenary of the National Academy of Sciences of Ukraine and the S.P.Timoshenko Institute of Mechanics (1918 – 2018) and is meant as some addendum to the articles that are devoted to this anniversary. The list of the most important books published for the period of almost centenary scientific activity of workers of the S.P.Timoshenko Institute of Mechanics of the National Academy of Sciences of Ukraine is proposed. The structure of list includes preliminary information, then the generalized collective multi-volume monographs, classical monographs, textbooks, tutorials and some special products of publishing activity of institute workers. In total, this list counts 468 books. A considerable part of these books – 247 – is presented in the Library of Congress Online Catalog.